2004
DOI: 10.3402/tellusb.v56i2.16414
|View full text |Cite
|
Sign up to set email alerts
|

Eddy correlation measurements of aerosol deposition to grass

Abstract: A B S T R A C T An experiment was conducted to measure aerosol turbulent fluxes to a grass field. A new high-flow-rate aerosol sensor was deployed from a tower to make eddy correlation (EC) measurements of aerosol turbulent flux and deposition velocity. The EC data were screened and analysed for uncertainties associated with advection, boundary layer growth, instrument separation and counting particles. An apparent bias in the aerosol flux due to particle hygroscopic growth was evaluated from chemical and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…Two approaches to correcting this problem, which differ in their choice of particle growth formula, are outlined in Kowalski (2001) and Vong et al (2004). We use here the model of Vong et al, which assumes a particle growth with humidity of…”
Section: Corrections and Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Two approaches to correcting this problem, which differ in their choice of particle growth formula, are outlined in Kowalski (2001) and Vong et al (2004). We use here the model of Vong et al, which assumes a particle growth with humidity of…”
Section: Corrections and Filteringmentioning
confidence: 99%
“…The hygroscopic growth parameter is assumed to be γ = 0.214, which Swietlicki et al (2000) suggest for "aged European air". As shown in Vong et al (2004), the deposition velocity correction is…”
Section: Corrections and Filteringmentioning
confidence: 99%
“…In daytime, when the average atmospheric relative humidity was 70-80% in this study, the hygroscopic growth of the most hygroscopic particles will be only 1-2%. The error due to hygroscopic growth (Fairall, 1984;Kowalski, 2001;Vong et al, 2004) can be estimated by calculating the saturation ratio flux (Fairall, 1984) and by assuming a particle size distribution in the Junge form (Junge, 1963). This error can be large when the slope of the number distribution is steep.…”
Section: Flux Measurementsmentioning
confidence: 99%
“…Five measurement studies conducted on grass (Wesely et al, 1977;Allen et al, 1991;Neumann and den Hartog, 1985;Nemitz et al, 2002;and Vong et al, 2004) were used to evaluate the accuracy of the parameterizations. In those studies, reported values of meteorological parameters, canopy properties, and particle size vary widely.…”
Section: Evaluation Of Dry Deposition To Grassmentioning
confidence: 99%
“…1 according to the five LUCs. Measurements conducted over grass by Wesely et al (1977), Neumann and den Hartog (1985), Allen et al (1991), Nemitz et al (2002), and Vong et al (2004) were used to evaluate the performance of the five parameterizations. For coniferous forest, modeled deposition velocities were compared with measurements from Lamaud et al (1994), Wyzers and Duyzer (1996), Gallagher et al (1997), Ruijgrok et al (1997), Buzorius et al (2000), Rannik et al (2000), Gaman et al (2004), Pryor et al (2007), and Grönholm et al (2009).…”
Section: An Evaluation Of the Dry Deposition Parameterizationsmentioning
confidence: 99%